A Study On Entreprise Loans Available At Commercial Banks In Malaysia For Small And Medium Scale Entreprises (SMEs) - Gopinathan, Dhranee Nathan (2006)
In this case study, a SWOT analysis was done to identify the strengths, weaknesses, opportunities and threads surrounding the SMEs hindering their access to financial resources.